2011
DOI: 10.1161/strokeaha.110.590786
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemodynamics Is Altered by Carotid Artery Disease and After Endarterectomy

Abstract: Background and Purpose-Carotid endarterectomy (CEA) has become a routine procedure to treat symptomatic carotid artery disease and reduce the risk of recurrent cerebral ischemic events. The purpose of this study was to use an arterial spin labeling dynamic magnetic resonance angiography technique to characterize intracranial hemodynamics before and after CEA. Methods-Thirty-seven carotid artery disease patients participated in this study, of whom 24 underwent magnetic resonance imaging before and after CEA. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…A larger study would be necessary to demonstrate whether these differences are significant, but similar changes in such parameters have been observed in other studies of patients with cerebrovascular disease. For example, the degree of carotid artery stenosis has been shown to be correlated with arrival time differences between hemispheres (30), and flow amplitude and time to peak, a parameter relating to bolus dispersion, in the ipsilateral MCA are altered following carotid endarterectomy (20). Although these studies and others (such as those by van Osch et al (31) and Okell et al (13)) have demonstrated maps relating to blood arrival time and/or dispersion, these used empirical approaches or less sophisticated models and most are not appropriate for the VEPCASL preparation used in this study where blood inflow is not observed in many voxels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger study would be necessary to demonstrate whether these differences are significant, but similar changes in such parameters have been observed in other studies of patients with cerebrovascular disease. For example, the degree of carotid artery stenosis has been shown to be correlated with arrival time differences between hemispheres (30), and flow amplitude and time to peak, a parameter relating to bolus dispersion, in the ipsilateral MCA are altered following carotid endarterectomy (20). Although these studies and others (such as those by van Osch et al (31) and Okell et al (13)) have demonstrated maps relating to blood arrival time and/or dispersion, these used empirical approaches or less sophisticated models and most are not appropriate for the VEPCASL preparation used in this study where blood inflow is not observed in many voxels.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we choose a gamma variate function for the dispersion kernel (Fig. 1b), which has been used previously to model the inflow of an injected bolus of contrast agent (19) or pulsed ASL preparation (20). Here, we aim to model the bolus dispersion rather than the entire bolus time course, but this function has the desirable properties of being causal and the ability to model a long tail, suitable for describing blood flowing in a laminar fashion.…”
Section: Theorymentioning
confidence: 99%
“…We have previously used arterial spin labeling dynamic angiography to show that CEA alters large vessel hemodynamics in the ipsilateral MCA (31). Following CEA, relative TTP and amplitude in the ipsilateral MCA were more similar to their contralateral counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…[47–85 years. ], M:F = 5:3) with atherosclerotic disease under an Institutional Review Board approved protocol and as part of a larger neuroimaging study . MRI data were acquired on a Siemens 3 Tesla (T) Trio scanner with gradient‐echo echo planar imaging (EPI): repetition time/echo time (TR/TE) = 1.5 s/30 ms, 78 volumes, 128 × 128 × 22 matrix, 1.7 × 1.7 × 5 mm 3 voxels, and diffusion weighted imaging (DWI): TR/TE = 4.4 s/93 ms, b‐values = 0, 1000 s/mm 2 (3 orthogonal directions), 27 slices, 1.6 × 1.6 × 3 mm 3 voxels.…”
Section: Methodsmentioning
confidence: 99%